Sports training of middle-distance runners, taking into account the peculiarities of the energy supply of their muscular activity - Klymenko, S. S.; Kadutskaya, L. A.; Domracheva, E. Yu.; Nesterenko, G. L. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the main pedagogical conditions necessary to improve the effectiveness of the competitive activity of middle-distance runners, taking into account the peculiarities of the energy supply of their muscular activity.